Roles Of Cell Compartments in the Variation of Firing Patterns Generated by Reduced Pacemaker Models of the Crustacean Stomatogastric Ganglion - Ye, W.J.; Liu, Sh.Q. (Нейрофизиология, 2016)
Endogenous bursters in central pattern generators (CPGs) generate rhythmic firing patterns
controlling regular movements in the organism. Based on a pacemaker kernel model of the
stomatogastric ganglion (SGG) of crustaceans, we constructed three reduced models, (i)
dendrite-reduced model (DRM), (ii) axon-reduced model (ARM), and (iii) primary neuritereduced model (PNRM). Similar firing patterns were observed in two models except the axonreduced one. Perturbing of various parameters in the models induced bifurcation phenomena
in the occurrence of interspike intervals (ISIs), which depicted variation of the firing patterns.
By comparing and analyzing two-dimensional parameter planes derived from the above
different models, the effects of compartments on varying firing patterns were detected. In
particular, a different kind of period-doubling transition mode of firing patterns, which varied
via a ring-shape mode, was found. Ендогенні компоненти центральних генераторів патернів
(ЦГП), відповідальні за контроль певних стандартних моторних феноменів в організмі, генерують ритмічні групи
розрядів. Базуючись на ядерній моделі пейсмекерів у стоматогастричному ганглії (СГГ) ракоподібних, ми сконструювали три редуковані моделі – модель з редукованими дендритами (ДРМ), модель з редукованим аксоном (АРМ) та
модель з редукованим первинним нейритом (ПНРМ). У двох
моделях, за виключенням АРМ, спостерігались однакові патерни розрядів. Змини різних параметрів моделей призводили до появи біфуркаційних феноменів у послідовностях
міжімпульсних інтервалів, що віддзеркалювалось у варіаціях патернів розрядів. У перебігу порівняння двовимірних
площин параметрів, отриманих для різних моделей, вдалось
ідентифікувати впливи компартментів на варіацію параметрів розрядів. Зокрема, було встановлено специфічний вид
перехідного режиму подвоєння періоду в патернах, варіації
якого мали кільцеподібний характер.